2023
DOI: 10.3389/fendo.2023.1093691
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growth hormone on pediatric body composition: A systematic review

Abstract: BackgroundGrowth hormone (GH) affects metabolism and regulates growth in childhood. The most prominent feature of GH deficiency (GHD) in children is diminished height velocity that eventually leads to short stature. In adult-onset GHD, lean body mass (LBM) is reduced, and visceral fat mass (FM) increased. Beneficial effects of GH treatment on body composition in adults with GHD, including an increase in muscle mass and a decrease in FM, are well established. Relatively few studies have investigated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Nevertheless, this conversion of adipose tissue to lean body mass does not mean a reduction in weight. Studies in children have shown that there is a positive effect of this therapy on body composition, independent of weight and BMI [ 23 ]. In fact, Gnacińska et al found that young women with TS who had undergone GHT had lower percentages of fat tissue, but not lower BMI, when compared to those who were not given this treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this conversion of adipose tissue to lean body mass does not mean a reduction in weight. Studies in children have shown that there is a positive effect of this therapy on body composition, independent of weight and BMI [ 23 ]. In fact, Gnacińska et al found that young women with TS who had undergone GHT had lower percentages of fat tissue, but not lower BMI, when compared to those who were not given this treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%